Understanding the Effect of Retirement on Health: Mechanisms and Heterogeneity - Peter Eibich (Journal of Health Economics, 2015)
This paper investigates the mechanisms behind the health effects of retirement. Using a Regression Discontinuity Design to exploit financial incentives in the German pension system for identification, I find that retirement improves subjective health status and mental health, while also reducing outpatient care utilization. I explore a wide range of health behaviors, time use, and effect heterogeneity as potential mechanisms. Relief from work-related stress and strain, increased sleep duration as well as more frequent physical exercise seem to be key mechanisms through which retirement affects health.
Additional information: This is the preprint of an article published in Journal of Health Economics 43 (2015), pp. 1-12, available online at: http://dx.doi.org/10.1016/j.jhealeco.2015.05.001
Keywords: I12; J14; J26; 330; Retirement; Health; Regression Discontinuity Design; Health behavior; Healthcare; Gesundheitsfürsorge; Rentner; Regression; Methode